Educational Hybridity and Ideological Negotiation in Integrated Islamic Kindergartens in Indonesia - Nurus Shalihin; Firdaus Firdaus; Yulia Yulia; M. Yusuf (Jurnal Ilmiah Peuradeun, 2026)
The rapid expansion of Integrated Islamic Kindergartens (TK IT) in Indonesia reflects broader transformations in the relationship between religion, education, and state governance in contemporary Muslim societies. However, existing studies on Sekolah Islam Terpadu (SIT) have largely focused on curriculum implementation and educational management, with limited attention to how these institutions negotiate hybridity between Islamic ideology and formal state education systems. This study aimed to examine the forms and practices of hybridity within TK IT in Padang City, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving six TK IT affiliated with JSIT, ASESI, and non-affiliated institutions. Data were analyzed using thematic analysis based on the interactive model of Miles and Huberman. The findings revealed three dominant forms of hybridity: integrative hybridity in TK IT JSIT, selective-defensive hybridity in TK IT ASESI, and adaptive-pragmatic hybridity in non-affiliated TK IT. These forms of hybridity were reflected in curriculum integration, institutional governance, pedagogical practices, and moral regulation. This study contributes to hybridity scholarship by demonstrating that hybridity within Islamic education involves ideological negotiation, identity construction, and epistemological reconstruction. The findings also provide broader insights into contemporary debates on faith-based education, Islamic educational modernity, and state-religion relations in Muslim societies.